Mathematical model of on-demand route formation for public transport based on individual passenger requests in low-density population area - Svetlana S. Titova; Andrey V. Ostroukh (International Journal of Advanced Studies, 2025)
Background. The organization of public transport routes based on individual passenger requests (on-demand routes) using small-class buses in areas with low population density has become a pressing issue due to the necessity of improving the efficiency of transport systems under limited financial and material resources. Traditional regular route schemes often prove unprofitable and insufficiently convenient for residents of such territories, leading to decreased transport accessibility and deterioration of population living standards. Modern technologies and mathematical modeling enable the development of flexible and cost-effective solutions capable of adapting to the characteristics of low-density regions and minimizing costs associated with organizing transport services.